Pharmacognostical and Physico chemical Evaluation of Soya Seed Granules - Deepika Gupta, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Pharmacognostical and Physico chemical Evaluation of Soya Seed Granules